(untitled) (International Journal of Engineering and Computer Science, 2017)
Wireless senor networks comprise of tiny nodes with limited energy and computational resources. Sensor networks are usually installed in unattended volatile environments where they are exposed to sever security attacks. Attackers can generate two main types of attacks i.e. injection of false reports and false MACs. PVFS is a singular en-route filtering scheme which counters both the attacks. However, the number of MACs attached to each report is fixed in PVFS. In this paper, we propose a scheme that supports fuzzy adaptive choice of votes to be included in the report before forwarding it to the base station in probabilistic voting based filtering scheme. The proposed method attains better energy saving when the attacks are not very hostile in terms of their frequency of occurrence, which helps extend network lifetime.